MLA Handbook for Writers of Research Papers - Gibaldi, Joseph, 1942- (New York Modern Language Association of America, 1995)
This handbook, that can be used as a reference tool, is designed to introduce the researcher/writer to the customs of a community of writers who value scrupulous scholarship and the careful documentation, or recording, of research. Chapter 1 suggests some of the educational and intellectual purposes of research and describes the first steps in a scholarly process--choosing a project; using a library; producing a working bibliography, notes, outlines, and drafts; and avoiding plagiarism. Chapter 2 (focusing on clear writing) gives practical advice on such matters as spelling, punctuation, and the presentation of names, numbers, titles of works, and quotations. Chapter 3 gives guidelines on the physical format of the paper. Chapter 4 explains how to list sources at the end of a paper, while chapter 5 shows how to cite them in the text of a paper. Chapter 6 describes abbreviations that are useful in documentation and in certain other contexts. Appendix A lists notable reference works in specialized fields; and appendix B presents some systems of documentation other than MLA's. Additionally, this new edition explains how to use and how to cite electronic catalogs, central information systems, and CD-ROM and online databases; how to use computers to facilitate the writing of research papers; and how to cite electronic publications, including CD-ROMs, diskettes, magnetic tapes, and online databases. The handbook concludes with sample pages of a research paper that uses MLA style
Include Index
Keywords: Research -- Report writing -- Bibliographical citations